CADANGAN PROSPEKTIF ASURANSI JIWA BERJANGKA DENGAN HUKUM DE MOIVRE - Dini Ramadani; Johannes Kho; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the calculation of the prospective reserve for term life insurance with De Moivre’s law to someone with the age of x where the money will be paid only if the insurance client dies within the term of protection. Based on the calculation, this prospective reserve is influenced by single premium, present value of annuity due, and annual premium, for which the calculation is done using De Moivre’s law.